Barreras en la atención de la salud en niños con defectos congénitos atendidos mediante el programa AIVA. - Ibáñez-Morantes, Alba; Sarmiento-Acuña, Karen; Suárez-Obando, Fernando; Zarante, Ignacio (Revista de Salud Pública, 2023)
Objective To identify the barriers in health care in patients with visual and auditory congenital defects (CD) treated through the Comprehensive Care Program for Families with Orphan Diseases with Visual and/or Auditory Compromise (AIVA), in Bogotá D. C., Colombia. Materials and Methods Cross-sectional study carried out in 58 children diagnosed with CD with possible visual or auditory compromise. The study population was selected from the AIVA program database, and to obtain the data, parents or legal representatives were asked to take the children for an initial medical evaluation and answer an interview. The barriers were classified according to Tanahashi's effective coverage model and the data were analyzed using descriptive statistics; absolute and relative frequencies were calculated for the qualitative variables, and means and standard deviations or medians and interquartile ranges (according to the distribution of the data determined with the Shapiro-Wilk test) for the quantitative variables. Results 81.03% of parents or legal representatives expressed at least one barrier, the most frequent being availability (49.38%), followed by accessibility (32.24%), acceptability (11.83%) and contact (6.53%). Conclusion The majority of parents or legal representatives interviewed reported barriers to accessing health services. Given that these have a negative impact on the health of children with CI, joint interventions are required to reduce them and thus guarantee better health conditions in children with CI and auditory or visual impairment.